Quantification of beta-defensin copy number variable genes in relation to inflammation in diabetic patients - Yusoff, Maryam Jamielah (2015)
Beta-defensins is one of the predominant antimicrobial peptide which serves as the first line defence against broad spectrum of microbes, including fungi and some viruses. These peptides are encoded by beta-defensins gene; which is variable in copy number. Copy number variations (CNVs) of beta-defensins is present in healthy population. Nevertheless, studies from the past decades have found that beta-defensins gene CNVs also contributed to several inflammatory diseases. Therefore, the objective of this study is to investigate the relationship between copy number variation of beta-defensins with inflammatory condition in type 2 diabetes (T2D). It is hypothesised that copy number variation of beta-defensins contributes to development of T2D through modification of immune response products dosage that exert attacks on host cell that contributed to inflammatory condition in T2D patients. DNA samples from 146 control and 392 T2D individuals were extracted for this study. Beta-defensins copy number quantification was carried out by using paralogue ratio test (PRT107A and HSPD21 primers) and validated by indel polymorphism measurement (5DEL primer) and two microsatellite analysis (EPEV-1 and EPEV-3 primers). Based on the analysis, the copy number variation is more extensive in T2D population ranging between 1 and 12 copies; with copy number 1, 10 and 12 detected in nephropathy group, while in control population the copy number varies between 2 and 8 copies. However, the distribution of copy number are not statistically significant between T2D and control (p=0.209) and between those with and without nephropathy among T2D population (p=0.522). Despite the result, the white blood cell count between individuals with and without nephropathy from T2D population is significantly different (p=0.000). In conclusion, future studies are needed to further explore the true potential of copy number variation of beta-defensins gene towards development of nephropathy in T2D patients.